The Western Pacific Regional Framework to End TB: overview and critical reflection - K.H. Oh; F. Morishita; K. Rahevar; R-P. Yadav; H.T.G. Tran; G.B Marks; M.C Raviglione; B.J. Marais (IJTLD Open)
Despite notable progress, TB remains a critical public health challenge in the Western Pacific Region. To address this, the WHO developed the Western Pacific Regional Framework to End TB, which aligns with global health targets, such as the End TB Strategy and the Sustainable Development Goals. Here, we critically review the Framework, highlighting its strengths and ongoing challenges, with suggestions as to how it might adapt. Although the Framework offers a comprehensive strategy for reducing the TB burden, its success depends on effective implementation across diverse socio-economic contexts. Key obstacles include undiagnosed infectious TB cases, limited healthcare infrastructure, persistent inequities in access to TB services, and drug-resistant TB. The COVID-19 pandemic exacerbated these challenges, disrupting TB services and delaying progress towards 2030 targets. The Framework’s reliance on multisectoral partnerships and innovative technologies presents opportunities but requires substantial political commitment, sustained funding and system-wide health reforms. Additionally, gaps remain in addressing social determinants of TB. Ensuring equity, maintaining political will, and fostering international collaboration are essential to overcoming these barriers. Continuous evaluation and adaptation will be crucial in ensuring the Framework’s effectiveness in eliminating TB in the Region by 2030.